Pemurnian Bioetanol Hasil Fermentasi Nira Nipah Dengan Proses Distilasi-Adsorpsi Menggunakan Bentonit Teraktivas - Tafrikhatul Walidah; Chairul Chairul; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Indonesia has petroleum reserves about 9 billion barrels, which the average production rate is 0.5 billion barrels per year, and was predicted would be exhaust within 18 years. Government has ordered a program and policy to develop bioethanol and biodiesel for the energy crisis in Indonesia. It is targeted can be provide about 15-20% of the fuel for transportation and national industry in 2025. This research’s goals were to produce fuel grade ethanol by distillation-adsorption method, determined the effect of activation temperature of bentonite and the effect ratio of bentonite to bioethanol. The raw materials were bioethanol from nypa sap (8% ethanol content). The ethanol concentration was not too high, so it needed to improve its purity by distillation-adsorption process. The research was held in three phases, which were distillation of nypa sap’s bioethanol to 96% ethanol content, activation of bentonite, and distillation-adsorption using activated bentonite. Activation temperature of bentonite were 400oC, 500oC and the ratio of bentonite:bioethanol were 1:2; 1:3; and 1:4. The most effective process for the purification of bioethanol was distillation-adsorption at 500oC activated temperature and the ratio of bentonite:bioethanol was 1:2 with the purity is 99.5% and has been categorized as a fuel grade ethanolKeywords: bentonite, bioethanol, distillation-adsorption, fuel grade bioethanol, nypa sap